Low-dose, short course alteplase treatment of submassive pulmonary embolism: a case series from the National Institutes of Health Clinical Center. Issue 8 (December 2018) - Lozier, Jay N.; Elinoff, Jason M.; Suffredini, Anthony F.; Rosing, Douglas R.; Sidenko, Stanislav; Sherry, Richard M.; Metwalli, Adam R.; Sachdev, Vandana; Danner, Robert L.; Chang, Richard
Abstract : N/A: Guidelines-recommend thrombolytic therapy for pulmonary embolism in patients with severe hemodynamic compromise and low risk of bleeding. Thrombolytics in submassive pulmonary embolism have an unfavorable risk/benefit ratio and remain controversial. Based on our experience with extensive, lower extremity thrombi, nine patients with symptomatic, submassive pulmonary embolisms (five medical, four surgical) were treated with low-dose alteplase (<10 mg/day, infused over 6 h per treatment). Alteplase was delivered by pulse spray and/or directed or undirected central venous catheters depending on clot size and location. All patients improved symptomatically and as determined objectively by pulmonary artery pressures and/or imaging, though acute benefits ranged from substantial to modest. One surgical patient required re-exploration for bleeding at the site of a recent retroperitoneal lymph node dissection. This experience may help guide the design of a randomized controlled trial to determine the safety and efficacy of low-dose alteplase for submassive pulmonary embolism. Abstract : Supplemental Digital Content is available in the text